2022
DOI: 10.1088/1361-6595/ac525b
|View full text |Cite
|
Sign up to set email alerts
|

Radio-frequency biasing of ion acceleration grids with different propellants

Abstract: In order to ensure the space charge compensation of the plume, conventional ion thrusters need an additional neutralizer to release electrons. When a radio-frequency (RF) voltage is applied across the grid system instead of a direct-current (DC) voltage, the simultaneous extraction of ions and electrons is achieved, thereby a neutralizer is not required. In this paper, based on the non-uniform distribution of neutral gas density calculated using the angular coefficient method, the particle-in-cell Monte Carlo … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 50 publications
2
17
0
Order By: Relevance
“…The measured IEDFs showed a multi-peak profile and the main peak almost disappears with a wide energy spread (100-800 eV) when the measured DC self-bias voltage is 300 V [18,19]. In addition, the influence of different propellants on the plasma beam in RF acceleration is investigated [29]. The experimental and simulation results are consistent with the trend of the average ion velocity with the RF voltage amplitude.…”
Section: Introductionsupporting
confidence: 66%
“…The measured IEDFs showed a multi-peak profile and the main peak almost disappears with a wide energy spread (100-800 eV) when the measured DC self-bias voltage is 300 V [18,19]. In addition, the influence of different propellants on the plasma beam in RF acceleration is investigated [29]. The experimental and simulation results are consistent with the trend of the average ion velocity with the RF voltage amplitude.…”
Section: Introductionsupporting
confidence: 66%
“…In this section, we conduct experimental verification and the RF oscillation is detected in the RF ion thruster BHRIT-4, which has already been tested in our recent study of neutralizer-free extraction [43]. The BHRIT-4 has a beam extraction system, which is composed of a screen grid, an acceleration grid and a grid insulator.…”
Section: Experimental Verification Of Rf Oscillationmentioning
confidence: 99%
“…As an inert gas, krypton, which has smaller mass, smaller collision cross-sections and higher ionization potential compared to xenon, is much more abundant on Earth than xenon. Therefore, krypton has become one of the ideal alternative propellants to reduce the dependence on the expensive gases and has attracted extensive international attention [3,22,23]. Potrivitu et al systematically tested the low current hollow cathode with krypton and observed the mode transition under several operation conditions [22].…”
Section: Introductionmentioning
confidence: 99%